2020
DOI: 10.1037/cbs0000151
|View full text |Cite
|
Sign up to set email alerts
|

Sex trafficking of women and girls in a southern Ontario region: Police file review exploring victim characteristics, trafficking experiences, and the intersection with child welfare.

Abstract: Domestic sex trafficking is a growing crime in Canada, with the majority of victims being children and youth. Youth involved with Child Welfare (CW) are vastly over-represented among sex trafficking victims. Yet, it is poorly understood why these youth are so vulnerable, particularly within the Canadian context. The goal of the current study was to increase our understanding of the elevated risk status of CW involved youth who are victimized by sex traffickers, as well as explore routes into sex trafficking. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Six studies reference the significance of sex-trafficked youth coming from impoverished households with unmet financial needs (Bruhns et al, 2018; Corbett, 2018; Moore et al, 2020; Reed et al, 2019; Rosenblatt, 2014; Smith et al, 2009). In addition, involvement with child welfare and childhood experiences of physical, sexual, and emotional abuse is common across many of the reviewed articles (Baird et al, 2020; J. E. O’Brien, 2018; Perkins & Ruiz, 2017; Reed et al, 2019; Rosenblatt, 2014; Smith et al, 2009; Tidball et al, 2016; Williamson & Prior, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six studies reference the significance of sex-trafficked youth coming from impoverished households with unmet financial needs (Bruhns et al, 2018; Corbett, 2018; Moore et al, 2020; Reed et al, 2019; Rosenblatt, 2014; Smith et al, 2009). In addition, involvement with child welfare and childhood experiences of physical, sexual, and emotional abuse is common across many of the reviewed articles (Baird et al, 2020; J. E. O’Brien, 2018; Perkins & Ruiz, 2017; Reed et al, 2019; Rosenblatt, 2014; Smith et al, 2009; Tidball et al, 2016; Williamson & Prior, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…With the continuum framework as a background, findings of this review present an evidence-based understanding of pathways into STM which can inform prevention initiatives to eliminate recruitment. Prevention efforts may be most effective online, as online avenues were the most commonly cited location where a youth initially meets their trafficker or is recruited (Baird et al, 2020; Moore et al, 2020; J. E. O’Brien, 2018; J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of predominantly domestic sex trafficking cases, for example, they discussed the ways that anti-trafficking laws overly scrutinize and under protect racial and gender minority groups. Studies of youth who have been sex trafficked have explored the impact on their mental health [ 11 ], routes to recruitment and entrapment [ 12 ], and higher risk of those within the child welfare system [ 13 ]. The limited research on social services for those who have been sex trafficked in Canada has revealed gaps in the delivery of services including a dearth of transitional housing and safe shelters, in addition to barriers to accessing health care, a lack of culturally informed services, and fear of being arrested [ 14 ].…”
Section: Introductionmentioning
confidence: 99%